Physico-chemical characteristics and consumer preference of liberica coffee liqueur - Comia, Jennifer Tangalin; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philiuppines Diliman, 2010)
ABSTRACT Liberica coffee and lambanog are among the indigenous products that are unique in the Philippines and has export market potential. A product which combines the exotic flavors of kapeng barako and lambanog, in the form of a coffee liqueur may find a niche in the alcoholic beverage industry. This study was undertaken to determine the effect of three infusion times (5, 10, 15 d) and infusion strengths (5, 10, 15% w/v) in the development of Liberica coffee liqueur. Samples were evaluated in terms of their physico-chemical properties (pH, Total Acidity (TA), Total soluble solids (TSS) and alcohol content). Consumer acceptance test using 50 randomly selected untrained panelists, who drink alcohol, were recruited for this study. Regression analysis showed that both infusion time and strength had an effect on the physico-chemical properties of the liqueur. Infusion of Liberica coffee grounds in fresh lambanog over time increased the pH, TA and TSS of the prepared liqueur while the alcohol content decreased significantly. Consumer acceptability of the product on the other hand was mostly affected by the amount of coffee infused in lambanog. Increased bittnerness as infusion strength increased may have decreased the consumer acceptability. Good quality parameters were achieved for samples infused for a longer period of time and at lower infusion strength. An alcoholic formulation utilizing lambanog and kapeng barako would deliver beneficial effects, but significant formulation issues to achieve consumer acceptability need to be resolved.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Coffee; Liquor; Lambanog